THROMBOLYSIS IN THE TREATMENT OF ACUTE STROKE: IS THERE A ROLE FOR STREPTOKINASE WHEN TISSUE PLASMINOGEN ACTIVATOR IS NOT AVAILABLE? - Shuaib, Ashfaq; Mohammad, Askar; Sherin, Akhtar; Butcher, Ken; Khan, Khurshid; Tariq, Muhammad; Shuaib, Umar; Khan, Hiba; Khan, Adnan (Journal of Postgraduate Medical Institute, 2013)
Every year 350,000 people suffer an acute stroke in Pakistan. Treatment of acute stroke has not improvedsignificantly despite the availability of intravenous thrombolysis with tissue plasminogen activator (tPA).The drug is expensive and is offered to a selected few. Streptokinase (SK), a low cost alternativethrombolytic agent, is widely available in Pakistan and is utilized to treat patients with acute coronarysyndromes. Streptokinase was tested in acute stroke in the 1980's and found to be ineffective in ischemicstroke. This is likely due to trial design flaws, rather than the drug itself. Factors that may havecontributed to poor outcomes include a prolonged treatment window, inclusion of patients with establishedinfarction on CT scan, failure to treat excessive arterial pressures, a fixed dose of streptokinase andconcomitant use of antithrombotic medications. Given the lack of therapeutic alternatives we believe that aproperly designed trial in appropriate patient population utilizing stricter inclusion criteria, includingearly treatment with a lower dose of SK is warranted.